Unjuk Kerja Reaktor Cuscade Bentuk Kolom - Hary Sulistyo; Merry Ad'hadi (Forum Teknik, 2003)
AbstractSome heterogeneous reactions such as liquid-solid, liquid-liquid were undertaken in the stirred tank batch reactor. To change a batch process into flow process, plugflow resctor is the reactor with the similar performance to the batch reactor. However, it would be faced withproblem to attain the plug flow pattern. A cascade of ideally mixed reactor was reactor which has a similar performance u,ilh the plugflow reactor especiallyfor heterogeneous system.Experinrent was wrdertaken in the column which was divided into three sections. This is similar with the three mixed flow reactors. Sodium chloride was used qs a tracer and water as fluid flow. It was investigated two variables such os stited speed and ratio of impeller diameter to the distance ofthe cascade.In this paper, Bodenstein number of pipe flow reactor and the number of stages for the cascade were determined experinrentally from the residence time distribution of the tluid. It is shown that the results good agreement with the empirical equation proposed by Pawlowski (1962) and Elgeti (1996).